Kontroversi Qadha’ Shalat dalam Pemikiran Ibnu Hazm: Tinjauan Mufassir dan Muhaddis - Massolihin, Edi; Syifa’, Manzilu; as-Shidqi, M. Iqbal; Syafi'ie, A Musta'in (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2025)
This study examines the differing views of Ibn Hazm al-Andalusi and the majority of Islamic jurists regarding the obligation of making up missed prayers (qadha’ Shalat). This disagreement has caused confusion among Muslims regarding the ruling on qadha’ prayers. The main question is: To what extent can Ibn Hazm’s argument be justified through Qur'anic exegesis and hadith analysis? This study employs a comparative library research method, examining Ibn Hazm’s work, particularly Al-Muhalla, and comparing it with authoritative tafsir and relevant hadiths. The analysis reveals that Ibn Hazm’s interpretation is overly literal, neglecting context and the general principles of Islamic law. Therefore, his claim is considered methodologically weak. Most exegetes and hadith scholars affirm that qadha’ prayer remains obligatory if performed under conditions that align with Shariah law and the principle of ease (taysir).